2021
DOI: 10.9734/irjpac/2021/v22i330391
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Carcinogenicity of PCBs in Soil Contaminated with Transformer Oil in Selected Locations in Jos, Plateau State Nigeria

Abstract: Soil from the vicinity of transformers installation in different locations in Jos, Plateau State was investigated for Polychlorinated Biphenyls (PCBs). The assessment was carried out for both total PCBs and congeners using Agilent 6975 GC-MS in ten different locations. The soil samples were extracted with 1:1 hexane- acetone in an ultrasonic bath, concentrated and cleaned with column chromatography using silica gel and hexane as eluting solvent. The result shows five locations were polluted with PCBs that exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This was attributed to the high level of contamination from different sources, as proved by the most deviated biological and radiological parameters against standards set by recognized local and international organizations. The concentration of heavy metals and microbiological loads in the water was significantly high and is a major roadblock to portable water for northerners (Ibrahim et al, 2020;Musa et al, 2020;Aliyu et al, 2020;Ogbozige et al, 2017;Haruna et al, 2016;Allamin et al, 2015;Ojo et al, 2014). Chemical and microbial contamination of the water was attributed to the high rate of population growth and several anthropogenic activities, as well as lack of access to enough water for sanitation and hygiene (Odey et al, 2022;Raji et al, 2020;Emurotu and Habib, 2019;Fardami et al, 2019;Sunday et al 2019;Omotayo et al, 2017;Zubairu et al, 2016).…”
Section: The Present State Of Water Qualitymentioning
confidence: 99%
“…This was attributed to the high level of contamination from different sources, as proved by the most deviated biological and radiological parameters against standards set by recognized local and international organizations. The concentration of heavy metals and microbiological loads in the water was significantly high and is a major roadblock to portable water for northerners (Ibrahim et al, 2020;Musa et al, 2020;Aliyu et al, 2020;Ogbozige et al, 2017;Haruna et al, 2016;Allamin et al, 2015;Ojo et al, 2014). Chemical and microbial contamination of the water was attributed to the high rate of population growth and several anthropogenic activities, as well as lack of access to enough water for sanitation and hygiene (Odey et al, 2022;Raji et al, 2020;Emurotu and Habib, 2019;Fardami et al, 2019;Sunday et al 2019;Omotayo et al, 2017;Zubairu et al, 2016).…”
Section: The Present State Of Water Qualitymentioning
confidence: 99%
“…Even though PCBs are known to bioaccumulate, this problem needs to be resolved. [36,37] found that the overall PCBs content in soil from transformer installation sites in University of Port Harcourt and Jos metropolis was greater than 2.00 mg/kg. These statistics (Table 6) demonstrate that we are far less polluted than more developed countries like China and the US [38,39] when compared to other studies from around the world.…”
Section: Health Risk Assessmentmentioning
confidence: 99%